Narrowing the global surgical perspective: The big city bias - Nunez-Ordonez, Nicolas; Cabrera-Vargas, Luis Felipe; Ferrada, Paula; Vervoort, Dominique (The American journal of surgery, 2022)
1 Introduction Guaranteeing access and quality of care for common surgical problems in Low- and middle-income countries (LMICs) are the main concerns raised by the Lancet Commission on Global Surgery to reduce the disease burden and mortality risk related to common treatable surgical conditions and improving outcomes and equity in surgical care.1 It has been estimated that surgical conditions are responsible for up to 32% of the overall global burden of disease1 Therefore, introducing common surgical problems into the public health agenda is becoming a priority for most LMICs given that access to surgical care is fundamental for achieving adequate population health as well as social and economic growth.1 The Lancet Commission has proposed 6 core indicators to be monitored across the world by public health organizations1: According to the World Bank, our country Colombia is a MIC with a significant number of people living under poverty.3 The General Health and Social Security System (SSS) has been a major advance towards guaranteeing universal healthcare coverage in our country through mandatory affiliation to either a contributing or subsidized regimen. Beyond our country, this phenomenon is likely true in all those nations that resemble the Colombian politic, social, and economic structure (e.g., other Latin-American countries). [...]we believe that the broad Lancet indicators should be used wisely when analyzing highly centralized nations, as big cities need a detailed, narrow approach and cannot be considered as a whole in nation-wide resource distribution.